A multicentre, prospective cohort study of handsewn versus stapled intracorporeal anastomosis for robotic hemicolectomy. (28th February 2022) - Harji, Deena; Rouanet, Philippe; Cotte, Eddy; Dubois, Anne; Rullier, Eric; Pezet, Denis; Passot, Guillaume; Taoum, Christophe; Denost, Quentin
Abstract: Aim: Robotic right hemicolectomy is gaining in popularity due to the recognized technical benefits associated with the robotic platform. However, there is a lack of standardization regarding the optimal anastomotic technique in this cohort of patients, namely stapled or handsewn intra‐ or extra‐corporeal anastomosis. The ergonomic benefit associated with the robotic platform lends itself to intracorporeal anastomosis (ICA). The aim of this study was to compare the short‐term clinical outcomes of stapled versus handsewn ICA. Method: A multicentre prospective cohort study was undertaken across four high‐volume robotic centres in France between September 2018 and December 2020. All adult patients undergoing an elective robotic right hemicolectomy with an ICA performed and a minimum postoperative follow‐up of 30 days were included. The primary endpoint of our study was anastomotic leak within 30 days postoperatively. Results: A total of 144 patients underwent robotic right hemicolectomy: 92 (63.8%) had a stapled ICA and 52 (36.1%) a handsewn ICA. The operative indication was adenocarcinoma in 90% with a stapled ICA compared with 62% in the handsewn ICA group ( p < 0.001). The overall operating time was longer in the handsewn ICA group compared with the stapled ICA group (219 min vs. 193 min; p = 0.001). The anastomotic leak rate was 3.3% in stapled ICA and 3.8% in handsewn ICA ( p = 1.00). There was no difference in the rate or severity of postoperative morbidity. Conclusion: ICA robotic hemicolectomy is technically safe and is associated with low rates of anastomotic leak overall and equivalent clinical outcomes between the two techniques.